Assessing the Blind Spot Zones of Passenger Cars - M. A. Mohamad Radzi; N. F. Paiman; Y. Ahmad; M. S. Solah; A. Shabadin; N. S. Azman (Journal of the Society of Automotive Engineers Malaysia, 2022)
Blind spots can still cause problems, even in circumstances where visibility is perfect and optimal for driving. Therefore, it is crucial to understand the Blind Spot Zone (BSZ), particularly its associated parameters, in order to create an effective system that is successful at detecting approaching vehicles and alerting the driver. It is also essential to understand that the size and locations of blind spots vary depending on various factors. Therefore, this study is aimed to evaluate the blind spot zones of passenger vehicles from a driver’s perspective. A systematic approach using a grid-based technique is proposed to model the BSZ. An experiment was conducted using a commonly used passenger car in Malaysia with a total of 30 cars which are classified into five segments: A, B, C, D, and 4x4. Each car’s BSZ area was identified, and the viewing angles of the driver were measured for both sides, driver, and passenger, respectively. As a result, the cars in segments A and B had the largest average blind spots, while the cars in segments C, D, and 4x4s had the widest viewing angles. In addition, it was found that the typical blind spot area on the passenger side is larger than the driver’s side.